2015
DOI: 10.1016/j.virusres.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of a natural strain of woodchuck hepatitis virus, WHVNY, to induce acute infection in naive adult woodchucks

Abstract: Woodchuck hepatitis virus (WHV) is often used as surrogate to study mechanism of HBV infection. Currently, most infections are conducted using strains WHV7 or WHV8 that have very high sequence identity. This study focused on natural strain WHVNY that is more genetically distant from WHV7. Three naive adult woodchucks inoculated with WHVNY developed productive acute infection with long lasting viremia. However, only one of two woodchucks infected with WHV7 at the same multiplicity demonstrated productive liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Our results suggested (i) that hepadnavirus cell-to-cell spread and superinfection continue during chronic hepadnavirus infection and (ii) that spread and superinfection, while being limited, still may represent the determinants of maintenance of chronic infection (15). In a separate study, we compared strains WHV7 and WHVNY and concluded that the two strains were quite similar in terms of their replication parameters and the ability to induce productive acute infection in naive adult woodchucks (16). This result was consistent with the interpretation that the observed limited efficiency of WHVNY superinfection in vivo (15) was not mediated by the properties of WHVNY virions but rather reflected the properties of hepatocytes residing in livers chronically infected with WHV7.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…Our results suggested (i) that hepadnavirus cell-to-cell spread and superinfection continue during chronic hepadnavirus infection and (ii) that spread and superinfection, while being limited, still may represent the determinants of maintenance of chronic infection (15). In a separate study, we compared strains WHV7 and WHVNY and concluded that the two strains were quite similar in terms of their replication parameters and the ability to induce productive acute infection in naive adult woodchucks (16). This result was consistent with the interpretation that the observed limited efficiency of WHVNY superinfection in vivo (15) was not mediated by the properties of WHVNY virions but rather reflected the properties of hepatocytes residing in livers chronically infected with WHV7.…”
mentioning
confidence: 77%
“…All experimental manipulations of animals have been performed under protocols approved by the Institutional Animal Care and Use Committee. Woodchucks F7386, M7297, and M7391 received as inoculum serum-derived WHV collected from woodchuck F6693 (16) at the peak of viremia during acute infection (week ϩ7 after inoculation). Animals M7393, F7238, and M7379 were infected with serum WHV harvested from woodchuck M1001 at the stage of early chronic infection (12 months postinoculation), when HCC was not yet developed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations